Novel two degree of freedom model matching controller for set-point tracking in MIMO systems. (July 2017) - Beevi, P. Febina; Kumar, T.K. Sunil; Jacob, Jeevamma; Beevi, P. Delina
Abstract: A control scheme is proposed in this paper that introduces a two degree of freedom (2-DOF) controller for tracking the desired trajectory of a multi-input multi-output (MIMO) system, by implementing an original method that infuses three techniques, such as the model order reduction, optimization and the approximate model matching techniques. The desired specifications for achieving set-point tracking may be embodied in the form of a transfer function matrix. The proposed method not only ensures the stability of the closed loop system with designed 2-DOF controller, but also satisfies the required performance criteria. This method is cost-effective, computationally simple, easy to implement and can be used in the design without any restrictions in the structure/order of the model's closed loop transfer function or 2-DOF controller. Simulation results demonstrate the effectiveness of the developed method.